2021
DOI: 10.3390/brainsci11060687
|View full text |Cite
|
Sign up to set email alerts
|

Antisocial Personality Problems in Emerging Adulthood: The Role of Family Functioning, Impulsivity, and Empathy

Abstract: International research has evidenced the key role played by adults’ and adolescents’ family functioning, impulsivity, and empathy in antisocial personality problems. To date, no study has assessed the complex interaction between these variables during emerging adulthood. This study aimed to explore the possible interplay between antisocial personality problems, the quality of family functioning, impulsivity, and empathetic problems in a community sample of 350 emerging adults. Descriptive, correlational, hiera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 88 publications
(161 reference statements)
2
17
0
1
Order By: Relevance
“…Overall, these findings supported the evidence that, during late adolescence/young adulthood, individuals become greater independent and autonomous from their parents and more oriented on the development of personal identity and relationships with their peers [13,125]. Although the relationship with parents continues to assume a crucial support role [126][127][128]-as our findings have also shown-attachment to peers become their essential secure base and source of emotional support [129][130][131]. Consequently, in line with our findings, during this developmental stage, insecure attachment to peers represents the strongest predictor for psychopathological problems, compared to insecure attachment to parents [132,133].…”
Section: Indirect Effects Of Attachment To Parents and Peers Via Alexithymiasupporting
confidence: 71%
“…Overall, these findings supported the evidence that, during late adolescence/young adulthood, individuals become greater independent and autonomous from their parents and more oriented on the development of personal identity and relationships with their peers [13,125]. Although the relationship with parents continues to assume a crucial support role [126][127][128]-as our findings have also shown-attachment to peers become their essential secure base and source of emotional support [129][130][131]. Consequently, in line with our findings, during this developmental stage, insecure attachment to peers represents the strongest predictor for psychopathological problems, compared to insecure attachment to parents [132,133].…”
Section: Indirect Effects Of Attachment To Parents and Peers Via Alexithymiasupporting
confidence: 71%
“…[ 16 ] that have shown a deterioration in parents’ psychological well-being due to COVID-19 pandemic, which significantly affected children’s psychological well-being through the resulting increase of parenting stress levels [ 5 , 29 , 53 ]. In this field, clinicians and researchers rooted in the Developmental Psychopathological framework have widely suggested that parental psychopathological difficulties may affect children’s emotional-adaptive functioning in a cascading way [ 64 ], from the transmission of predisposition to (epi-)genetic vulnerabilities [ 65 , 66 ], to children’s exposure to an adverse affective family environment [ 67 , 68 , 69 ], including poor quality of parent-child interactions [ 30 , 70 , 71 ], family functioning [ 72 , 73 , 74 , 75 ], and high parenting stress levels [ 76 , 77 ]. Recently, cascading effects have also been suggested in the context of COVID-19: The psychological impact of COVID-19 on parents may negatively influence parenting and related stress levels, which in turn may place children at higher risk of psychopathological symptoms [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with our hypotheses, in the present study, boys showed higher levels of Internet addiction than girls. Research in the field of Internet addiction among emerging adults has shown mixed results, with some studies evidencing higher rates of prevalence among males [ 113 ] while other studies have reported no sex differences [ 117 , 118 ] or that females were more likely to be affected by Internet addiction than males [ 119 , 120 ]. However, in line with our findings, the research specifically focused on Internet addiction during the COVID-19 pandemic has also shown a higher risk among males [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the emerging adults’ family context was not considered. In fact, several studies have highlighted the psychological impact of the family on the origin of the youths’ mental health [ 105 , 113 , 117 , 151 , 152 ].…”
Section: Discussionmentioning
confidence: 99%